2007
DOI: 10.17705/1cais.02014
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Gender Balance of IS Journal Editorial Positions

Abstract: An analysis of 18,854 editorial positions on IS journals was undertaken to examine the perceived gender balance of those positions as an indication of their contribution towards a positive role model for females considering an IS academic career. The nature and extent of perceived gender balance is examined in terms of overall composition of editorial positions, journal prestige and the specific area within IS covered by a journal. The results indicate that perceived gender balance of editorial positions refle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Since the original publishing, research on the topic of the barriers faced by women in IS has been limited. What has been published on the topic of gender and barriers/turnover in IS ranges from a discussion of parity in academia (Johnson et al, 2008;Lamp, 2007) to critical theory (Reid et al, 2010) to gender identity in the IS field (Adam et al, 2006;Woszczynski and Shade, 2010). With regard to retention and turnover scholars have utilized the Permission to make digital or hard copies of all or part of this work for personal or classroom use is granted without fee provided that copies are not made or distributed for profit or commercial advantage and that copies bear this notice and the full citation on the first page.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since the original publishing, research on the topic of the barriers faced by women in IS has been limited. What has been published on the topic of gender and barriers/turnover in IS ranges from a discussion of parity in academia (Johnson et al, 2008;Lamp, 2007) to critical theory (Reid et al, 2010) to gender identity in the IS field (Adam et al, 2006;Woszczynski and Shade, 2010). With regard to retention and turnover scholars have utilized the Permission to make digital or hard copies of all or part of this work for personal or classroom use is granted without fee provided that copies are not made or distributed for profit or commercial advantage and that copies bear this notice and the full citation on the first page.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To sum up regarding who publishes, we see little change in the balance of gender over the ten year period with a little over one in four publications including a woman author. There is evidence to suggest that this reflects the number of women academics (Lamp 2007). It is nevertheless a little disheartening not to see any improvement in this number.…”
Section: Further Reflectionsmentioning
confidence: 96%
“…The combination of these two informative sessions set the stage for a deeper, more informed discussion. Finally, since previous research has already identified the lack of women in the higher ranks of journal editorships and authorships (Lamp 2007), the organizers convened a panel of available editor-in-chiefs of top IS journals to help identify how attendees could get more involved in journal editing and publishing.…”
Section: Pre-icis Workhop: "Advancing Women In Is"mentioning
confidence: 99%
“…The number of women in information systems (IS) has been declining for over twenty-five years, and this decrease exceeds that found in other STEM disciplines such as math and the sciences (Dubow 2010;Loiacono et al 2013;Ramsey & McCorduck, 2005). In the academic community, this disparity has manifested in a significantly lower percentage of women journal editorships, the underrepresentation of women on conference panels and committees, and their absence in top-tier IS journal publications (Lamp 2007) even though women make up approximately 25 percent of the IS discipline (and approximately 29% of the AIS). Adding to the problem is the perception by some in the IS community that there is no problem.…”
Section: Introductionmentioning
confidence: 99%